Using the Body When There Are No Words for Feelings: Alexithymia and Somatization in Self-Harming Adolescents - Raffagnato, Alessia; Angelico, Caterina; Valentini, Perla; Miscioscia, Marina; Gatta, Michela (Frontiers in Psychiatry, 2020)
The present case-control study aimed to investigate the relationship between alexithymia and somatic complaints in the psychopathological setting of Non-suicidal self-injury (NSSI). A clinical sample of 134 adolescents (115 females; 85.5%) from 12 to 18 years old engaging in NSSI was compared with a control group of 243 high-school students (157 females; 64.6%) from 13 to 18 years old. Data were collected using two questionnaires: The Youth Self-Report 11-18 and the 20 Toronto Alexithymia Scale. In both cases and controls, the presence of somatization and alexithymia was associated with more severe psychopathological problems. Analyses were conducted to explore the association between somatic disorders and alexithymia. In the clinical group, somatic complaints were reported by 95.9% of alexithymic individuals, whereas only 44.3% of alexithymic adolescents reported somatic complaints. A one-way relationship emerged between somatization and alexithymia: while alexithymia would seem to be a factor associated with self-injury, somatic disorders were strongly associated with alexithymia, but not necessarily with self-injury. Among the self-harming adolescents, those with both alexithymia and somatization had a more severe psychopathological picture than the individuals with alexithymia but no somatization. This would suggest that, in the setting of NSSI, greater difficulty with identifying feelings is associated with somatization, and alexithymia would be an attribute common to self-harming behavior and somatization, both of which are characterized by the body being used to express psychological and emotional problems. Future research could further investigate alexithymia in self-harming individuals, in relation to any presence or absence of somatic disorders, with longitudinal assessments on any differences in their manifestation of self-injury and its psychopathological correlates.